2017
DOI: 10.1089/neu.2015.4227
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of Locomotion in Response to Hindlimb Muscle Stretch at Acute and Chronic Time Points after a Spinal Cord Injury in Rats

Abstract: After spinal cord injury (SCI) muscle contractures develop in the plegic limbs of many patients. Physical therapists commonly use stretching as an approach to avoid contractures and to maintain the extensibility of soft tissues. We found previously that a daily stretching protocol has a negative effect on locomotor recovery in rats with mild thoracic SCI. The purpose of the current study was to determine the effects of stretching on locomotor function at acute and chronic time points after moderately severe co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(39 citation statements)
references
References 58 publications
5
33
1
Order By: Relevance
“…As in previous studies, these animals achieved some locomotor recovery over the weekends when they were not stretched. [186,218] However, one stretching session (Monday morning) was enough to again reduce the BBB scores to below 4 ( Fig.1). Lack of hindlimb movement was further confirmed with the more objective kinematic and gait analysis.…”
Section: Resultsmentioning
confidence: 97%
See 4 more Smart Citations
“…As in previous studies, these animals achieved some locomotor recovery over the weekends when they were not stretched. [186,218] However, one stretching session (Monday morning) was enough to again reduce the BBB scores to below 4 ( Fig.1). Lack of hindlimb movement was further confirmed with the more objective kinematic and gait analysis.…”
Section: Resultsmentioning
confidence: 97%
“…Contrary to our hypothesis, dynamic stretching dramatically disrupted locomotor function reducing BBB scores to levels similar to those of static stretching even though the total amount of stretch that the animals received on a daily basis was less (20 seconds less/stretch) than in our previous studies. [186,218] Histological analysis of the muscles revealed that for the ankle extensor MG the group sacrificed two hours after stretching had elevated numbers of centralized nuclei (8%) as compared to the rats sacrificed four weeks later (~4%)…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations